Artificial mixed microbial system for polycyclic aromatic hydrocarbons degradation - Cui, Jia-Qi; He, Zhi-Qiang; Ntakirutimana, Samuel; Liu, Zhi-Hua; Li, Bing-Zhi; Yuan, Ying-Jin (Frontiers in Microbiology, 2023)
Polycyclic aromatic hydrocarbons (PAHs) are environmental pollutants with major risks to human health. Biological degradation is environmentally friendly and the most appealing remediation method for a wide range of persistent pollutants. Meanwhile, due to the large microbial strain collection and multiple metabolic pathways, PAH degradation via an artificial mixed microbial system (MMS) has emerged and is regarded as a promising bioremediation approach. The artificial MMS construction by simplifying the community structure, clarifying the labor division, and streamlining the metabolic flux has shown tremendous efficiency. This review describes the construction principles, influencing factors, and enhancement strategies of artificial MMS for PAH degradation. In addition, we identify the challenges and future opportunities for the development of MMS toward new or upgraded high-performance applications.